The Effect of Sonic Bloom Fertilizing Technology on The Seed Germination and Growth of Acacia mangium Willd Seedling - Mulyadi A T; Poppy Mairani; Ade Sunandar (Jurnal Manajemen Hutan Tropika, 2012)
Acacia mangium Willd is one of the promising wood species, it is a fast growing species and can be used as raw materials for pulp, furniture and wood working. Musi Hutan Persada Company has planted Acacia mangium Willd in large scale for pulp processing raw materials and for wood working industry. The faculty of forestry of the Nusa Bangsa University in collaboration with the Musi Hutan Persada have examined the effect of “Sonic Bloom” to the Acacia mangium Willd germination and seedling growth. The results of the research are the following : (1) The seed germination with “Sonic Bloom” provided percented of germination of 82%, better than those without “Sonic Bloom”, i.e. only 34%; (2) With Sonic Bloom,  the height of 80-days old seedling is 129.6 cm higher than those without “Sonic Bloom”of only 90.7 cm; (3) the diameter of 80-days old seedling with “Sonic Bloom” is 0,24 cm higher than those without “Sonic Bloom” harving diameters of only 0.19 cm. The study concludes that sonic bloom treatment is very useful for the seed germination and the growth of Acacia mangium Willd seedling.